Interruptions, visual cues, and the microstructure of interaction: Four laboratory studies. Issue 103 (July 2017) - Weng, Michael; Huber, Stephan; Vilgan, Elizabeth; Grundgeiger, Tobias; Sanderson, Penelope M.
Abstract: Visual cues relating to an interrupted task can help people recover from workplace interruptions. However, it is unclear whether visual cues relating to their next steps in a primary task may help people manage interruptions. In a previous intensive care unit simulation study, Grundgeiger et al. (2013) found that nurses performing equipment checks were more likely to defer an interruption from a colleague if they could see the next steps of their task on the equipment screen. We abstracted some elements of the simulation study into a controlled laboratory study to test whether visual cues support interruption management. Participants' primary task was to verify a set of linked arithmetic equations presented on a computer page. From time to time, an animated virtual character interrupted the participant to mimic a social interruption, and the participant chose whether or not to defer a response to the interruptions until they finished their page of equations. In four experiments, the independent variable was visual cue (cue versus no cue) and the primary outcome was the proportion of interruptions from the character that the participant deferred so that she or he could complete the page of equations. Experiment 1 (in English) suggested that the visual cue made participants more likely to defer the interruption. However, a potential confound noted in Experiment 1 was eliminated in Experiment 2 (also in English) and the effect of the visual cue disappeared. Experiment 3 (in German) tested a different way to remove the confound and replicated the results of Experiment 2. Finally Experiment 4 (in German) restored the confound and replicated the results of Experiment 1. Participants' decisions to defer interruptions can depend on apparently minor properties of their primary task. Highlights: Visual cues about upcoming primary tasks may encourage people to defer interruptions. In four experiments we tested the role of cues vs. no cues during the interruption lag. Cues were confounded with a greater opportunity to make progress in the primary task. Deferrals were no more frequent with cues vs. no cues if confound was removed. Interruption–management microstrategies revealed sensitivity to time or memory costs.